2014
DOI: 10.3390/s140203604
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Polymer-Based Nanohybrid Transducers: A Potential Route to High Sensitivity and Selectivity Sensors

Abstract: The development of novel sensing materials provides good opportunities to realize previously unachievable sensor performance. In this review, conducting polymer-based nanohybrids are highlighted as innovative transducers for high-performance chemical and biological sensing devices. Synthetic strategies of the nanohybrids are categorized into four groups: (1) impregnation, followed by reduction; (2) concurrent redox reactions; (3) electrochemical deposition; (4) seeding approach. Nanocale hybridization of condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 74 publications
1
45
1
Order By: Relevance
“…Since the discovery of the band-gap fluorescence of SWCNT in 2002 [16], these nanomaterials have been extensively used for optical sensing, particularly for biological systems. Their fluorescence in the NIR region (between 820 and 1600 nm), inherent photostability and tissue transparency have been exploited in the development of in vitro and in vivo sensors [17][18][19]. In addition, recent studies have demonstrated that SWCNT can act collectively as quenchers for different kinds of fluorophores, such as pyrene, porphyrins, and chromophores [20], via covalent or non-covalent interactions.…”
Section: Introductionmentioning
confidence: 98%
“…Since the discovery of the band-gap fluorescence of SWCNT in 2002 [16], these nanomaterials have been extensively used for optical sensing, particularly for biological systems. Their fluorescence in the NIR region (between 820 and 1600 nm), inherent photostability and tissue transparency have been exploited in the development of in vitro and in vivo sensors [17][18][19]. In addition, recent studies have demonstrated that SWCNT can act collectively as quenchers for different kinds of fluorophores, such as pyrene, porphyrins, and chromophores [20], via covalent or non-covalent interactions.…”
Section: Introductionmentioning
confidence: 98%
“…Recent progresses in the area of electroactive polymers and the controlled synthesis of these polymeric materials have allowed the rational design and preparation of new biological biosensor systems with wide range of applications such as health care, immunosensors, DNA sensors, environmental monitoring, and food analysis. CPs are most amenable to biosensors as they can act as matrix for the immobilization or localization of biological entity responsible for recognition of analyte or can be used in the sensing mechanism as a physicochemical transducer to convert biochemical signal to digital electrical signal or can be an interface to act as self‐contained electron transport mediator during enzymatic reactions between an enzyme and the final electrode . So, CP emerged as an important component mediating, transducing, and more recently amplifying the responses signifying specific analyte's presence.…”
Section: Application In Biosensorsmentioning
confidence: 99%
“…In general, the disadvantage of such a method is the poor control of the size, morphology, and orientation of the CP nanostructures [6], which has prevented wide utilization of molecular template synthesis. In order to resolve the limitations of this method (the equilibrium shape and size of surfactant aggregates), numerous factors must be considered, such as the geometry of the template molecules (for example, in the case of micelles, the length of the surfactant tail in the hydrophobic core and the volume and effective area of each surfactant head group) [1].…”
Section: Molecular Template Approachmentioning
confidence: 99%
“…A great deal of effort has been made to develop various types of CP-based sensors [4,6,8,101,[184][185][186]. The signal transduction mechanism of CPs for sensor applications has mostly relied on changes in the electrical properties.…”
Section: Sensorsmentioning
confidence: 99%